Redes de interacciones ecológicas entre aves frugívoras-plantas en un gradiente de degradación del bosque estacionalmente seco de Zapotillo - Maldonado Aguilar, Jordy Lauro (2025)
Ecological interaction networks are indicators of the current health status of ecosystems, regulate the functioning of megadiverse systems and provide ecosystem services. They are classified into positive (mutualisms) and negative (antagonisms). The interactions between frugivorous birds and plants stand out for their mutualistic relationship, where birds play the role of restoration agents, promoting the colonization of plants and the regeneration of forests in a natural way. In the seasonally dry tropical forests (BTES) of Zapotillo, chronic disturbance has been identified as a crucial factor in the erosion of biological diversity due to anthropogenic pressures. The study focused on understanding and evaluating the structure of the interaction networks between frugivorous birds and plants in the degradation gradient of the Zapotillo BTES. For the record of interactions, nine sampling points were established in the five states of degradation: natural, semi- natural, shrubby, simplified and arid where trees and shrubs with fleshy fruits were identified as sampling points of the interactions, performed during the winter season. Twenty-three bird species were identified that interacted with six plant species present in the sampling, and three indices of the network along the degradation gradient as nesting, asymmetry and connectance were calculated. The nesting rate was significantly higher in the simplified and shrub-dominated state (63,71), while all states showed negative asymmetry, as for connectance, the natural state had the lowest value (0,27). Although the indices did not vary widely between the states of degradation, the difference could be related to the low presence of plants in fruiting, highlighting species such as Allophylus cf. Psilospermus, Coccoloba ruiziana, Citharexylum poeppigii, Cordia lutea, Bursera graveolens and Solanum sp.